Study on Growth Mechanism of Cu Nanowires and Its Application as Transparent Conducting Electrode - Dedi Mardiansyah; Kuwat Triyana; Harsojo Harsojo (Indonesian Journal of Chemistry, 2019)
Cu nanowires (CuNWs) were synthesized in an aqueous solution at low temperature using ethylenediamine (EDA) as a capping agent and hydrazine as a reducing agent. This study investigated the growth of mechanism CuNWs and fabricated the transparent conducting electrode. For the growth mechanism of CuNWs, the study was conducted with an optical microscope, scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray diffraction (XRD). The performance of the transparent conducting electrode was studied with UV-Vis spectrometer and IV meters. CuNWs growth from Cu nanoparticles (CuNPs) in the solution. Transparent conducting electrode gave a sheet resistance of 48.8 Ohm/sq and the transmittance of 52.63%. The understanding of the growing mechanism of Cu nanowires is important for the development of CuNWs for alternative application as a transparent conducting electrode.